An Efficient MLFMA for Accurately Analyzing Electromagnetic Radiation and Coupling Characteristics of Large-scale Antenna Arrays Mounted on Platform - Yin, Lei; Ding, Ning; Hou, Peng; Lin, Zhongchao; Zhao, Xunwang; Jiang, Shugang; Jiao, Yongchang (Applied Computational Electromagnetics Society Journal (ACES), 2024)
A multilevel fast multipole algorithm (MLFMA) for analyzing electromagnetic radiation and coupling characteristics of large-scale antenna arrays mounted on the platforms is presented in this paper. Compared with the method of moments (MoM), the MLFMA can be used to calculate larger scale problems with limited resources. First, waveport model of the MLFMA based on the equivalence principle and mode matching theory is established to efficiently and accurately simulate the antenna array. Then, a preconditioning approach for solving the radiation problems with the waveports is designed to improve convergence of the MLFMA. An initial guess construction method is proposed to accelerate the MLFMA computation for the multi-excitation problems, which can reduce the iteration time by at least 50%. Numerical results demonstrate accuracy and efficiency of the proposed method.